AI Anchor, 5G, and Recommendation Algorithm: Interaction, Adoption, and Impact of Emerging Communication Technology - Jin, Xin; Jiang, Yanru; Zhang, Yidi; An, Zimeng; Ye, Qianying; Zhang, Yundi; Dai, Bin; Zhu, Chengzhang; Xiao, Yalong (The 2021 AEJMC Midwinter Conference, 2021)
As some of the most popular topics within communication technology research, AI in journalistic practices, 5G in human life, and recommendation algorithms in social media have been paid a lot of attention to the past 2019 to 2020. In this panel, we focus on the pattern of human-AI interaction, contributors and obstacles of 5G’s adoption, and the impact of the recommendation algorithm on communication structure and information diffusion model. In brief, discussing what role communication technology plays in human society.